Digital rights management in Turkish online music sector - (:unkn) unknown (My University, 2011)
With technological developments e.g. MP3 audio compression methods, and new hardwares e.g. portable media players, besides digital content and software, music consumption is increasing too. DRM (digital rights management) appeared to protect economically digital art and right owners against illegal file sharing and downloading. In this paper, we examined Turkish online music area, business models using DRM, related parties, associations, unions and web sites practicing these models. © 2011 IEEE.